2006
DOI: 10.1158/0008-5472.can-05-3390
|View full text |Cite
|
Sign up to set email alerts
|

In utero Exposure of Mice to Dibenzo[a,l]Pyrene Produces Lymphoma in the Offspring: Role of the Aryl Hydrocarbon Receptor

Abstract: Lymphoma and leukemia are the most common cancers in children and young adults; in utero carcinogen exposure may contribute to the etiology of these cancers. A polycyclic aromatic hydrocarbon (PAH), dibenzo [a,l]pyrene (DBP), was given to pregnant mice (15 mg/kg body weight, gavage) on gestation day 17. Significant mortalities in offspring, beginning at 12 weeks of age, were observed due to an aggressive T-cell lymphoblastic lymphoma. Lymphocytes invaded numerous tissues. All mice surviving 10 months, exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
102
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(110 citation statements)
references
References 54 publications
8
102
0
Order By: Relevance
“…A classification scheme (40) devised under the direction of the Mouse Models of Human Cancers Consortium has been published and can be used for comparison with the WHO classification of lymphomas (39). We have, for the first time in any animal model, documented that exposure of pregnant mice to a single dose of a potent PAH, DBP, results in a very aggressive T-cell lymphoma in the offspring beginning at 10 weeks of age (8)(9)(10). Our hypothesis is that maternal transfer to the fetus results in cyp1b1-dependent bioactivation to DBP-(−)-anti-(11R,12S,13S,14R)-dihydrodiol epoxide and other reactive metabolites of DBP in the thymus producing a number of DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A classification scheme (40) devised under the direction of the Mouse Models of Human Cancers Consortium has been published and can be used for comparison with the WHO classification of lymphomas (39). We have, for the first time in any animal model, documented that exposure of pregnant mice to a single dose of a potent PAH, DBP, results in a very aggressive T-cell lymphoma in the offspring beginning at 10 weeks of age (8)(9)(10). Our hypothesis is that maternal transfer to the fetus results in cyp1b1-dependent bioactivation to DBP-(−)-anti-(11R,12S,13S,14R)-dihydrodiol epoxide and other reactive metabolites of DBP in the thymus producing a number of DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, using DBP or 3-methylcholanthrene in models, in which either the dam or the fetus were Ahr "nonresponsive" or "responsive," it was shown that the responsive dam reduced the risk to the fetus apparently by decreasing the bioavailability through enhanced maternal metabolism and clearance (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations